Multimarket trading and the cost of debt: evidence from global bonds - Lubomir Petrasek (European Central Bank (ECB), 2010)
Global bonds are international securities designed to be traded and settled efficiently in multiple markets. This paper studies global bonds to examine the effects of multimarket trading on corporate bond liquidity, prices, and the cost of debt. Using a sample of primary and secondary market transactions matched by issuer, I find that global bonds command a significant liquidity and price advantage over comparable domestic bonds. On average, global bonds trade at yields 15 to 25 basis points below domestic bonds of the same issuers, with the difference being greater for speculative grade bonds and in times of crisis. Global issues are more liquid, as evidenced by several trade-based liquidity measures, but the liquidity advantage of global bonds does not fully explain the yield differential. The findings imply that international corporate bond markets are not fully integrated, and global bond offerings can reduce the cost of debt.
Keywords: G15; G12; G32; F36; 330; corporate bonds; Cost of debt; international financial markets; liquidity; Internationale Anleihe; Kapitalkosten; Internationaler Finanzmarkt; Internationale Unternehmensfinanzierung; Kapitaleinkommen; Eurobond; USA; Welt